Visions of the Good Life : Salvation, Church, and Mission in the Secular West - Abrahamse, Jan Martijn; Paas, Stefan; Schaeffer, Hans; Zwijze-Koning, Karen (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
There is something wrong with us and the world we find ourselves in. In the Christian tradition, the concept of God's salvation describes the divine intervention to overcome this brokenness. However, such language might easily be misunderstood in the increasingly secular West. To make the reality of the doctrine of salvation understandable, relevant, and attractive for Europeans in the West, we might begin to think of it more in terms of relationship, well-being, and wholeness. Using a Biblical term, salvation is about the Shalom of the Reign of God. This volume explores the lived salvation practices of faith communities and missions, and their conceptualisations in the West: how is the good life perceived and practiced? Contributors are Clive Marsh, Jan Martijn Abrahamse, Dejan Aždajić, K. Francis Adebayo, Philip Bartholomä, Janel Kragt Bakker, Nigel Rooms, Karen Zwijze-Koning, Hans Schaeffer, Berdine van den Toren-Lekkerkerker, Jack Barentsen, Chris James, Sake Stoppels, Annemieke de Jonge, Bert Roor, Evelien van Duffelen, Harvey Kwiyani, James Butler, Kathy Ross, Ross Lockhart, and Stefan Paas.